2011
DOI: 10.1007/s10072-011-0666-5
|View full text |Cite
|
Sign up to set email alerts
|

Do the quantitative relationships of synaptic junctions and terminals in the thalamus of genetic absence epilepsy rats from Strasbourg (GAERS) differ from those in normal control Wistar rats

Abstract: Abnormal functional properties of the thalamocortical connections were reported in the absence of epilepsy. The present study compares the ratios of terminals ('RL'-round vesicles, large terminals, 'RS'-round vesicles, small terminals and 'F'-flattened vesicles) and synapse in three first-order (ventrobasal, lateral geniculate and anteroventral) and in three higher-order (posterior, lateral posterior and mediodorsal) thalamic nuclei of genetic absence epilepsy rats from Strasbourg (GAERS) with our earlier quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Indeed, the Po in GAERS contains a higher number of driver terminals, as compared to healthy non-epileptic control rats. This difference was not found in other thalamic nuclei (Cavdar et al, 2012 ). Furthermore, higher-order nuclei like the Po, as compared to first order nuclei such as the VPM, have been demonstrated to be more prone to thalamic burst firing (Ramcharan et al, 2005 ), a property which is generally believed to be favorable for SWD generation (Avoli et al, 2001 ).…”
Section: Different Functional Contributions Of Network Structures Formentioning
confidence: 70%
“…Indeed, the Po in GAERS contains a higher number of driver terminals, as compared to healthy non-epileptic control rats. This difference was not found in other thalamic nuclei (Cavdar et al, 2012 ). Furthermore, higher-order nuclei like the Po, as compared to first order nuclei such as the VPM, have been demonstrated to be more prone to thalamic burst firing (Ramcharan et al, 2005 ), a property which is generally believed to be favorable for SWD generation (Avoli et al, 2001 ).…”
Section: Different Functional Contributions Of Network Structures Formentioning
confidence: 70%
“…in the Wistar rats and 19.2% in the GAERS [36,41] . This is in accord with the present results that an unexpectedly high number of GABAergic interneurons occurred in the VPM and VPL nuclei of the GAERS animals relative to the Wistar rats.…”
Section: Differences Between Wistar Rats and Gaersmentioning
confidence: 86%
“…The measurements were made by an observer who was blinded LGN sample section was published in our previous manuscript [36] , for which the same tissue blocks were used.…”
Section: Neuron Area Measurementmentioning
confidence: 99%
“…As far as the anatomo-morphological features of GABAergic neurons in cortico-thalamic networks are concerned, a recent study has shown a higher proportion of GABAergic cells in the ventroposteromedial (VPM) and ventroposterolateral (VPL) thalamic nuclei, the two subdivision of the VB, in 6–12 month old GAERS than in age-matched normal Wistar rats ( Cavdar et al., 2014 ), in contrast to the accepted view that in this rodent thalamic nucleus GABAergic interneurons are only sparse or absent ( Arcelli et al., 1997 , Harris and Hendrickson, 1987 , Houser et al., 1980 ). Moreover, a developmental decrease in the number of NRT GABA-positive and GABA-negative neurons has been described in GAERS at postnatal day 30 (P30) to P60 compared to normal Wistar rats ( Cavdar et al., 2013 ), whereas GABA-immunoreactive (GABA-IR) profiles in the GAERS VB shows a 3-fold increase at the same postnatal ages compared to Wistar rats ( Cavdar et al., 2012 ). In the γ 2 R43Q mouse model, a higher density of various GABAergic interneurons has been reported in S1, though paradoxically the ratio between putative excitatory and inhibitory neurons was found to be decreased ( Wimmer et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%